RANCANGAN TEKNIS DESAIN PUSH BACK PADA PENAMBANGAN BATUBARA PIT 10 DAN PIT 13 PT. KAYAN PUTRA UTAMA COAL KABUPATEN KUTAI KARTANEGARA KALIMANTAN TIMUR (Jurnal Geologi Pertambangan (JGP), 2017)
The purpose of this research is to design push back on mining pit13 and  pit10 for 12 months (June 2016 – June 2017) on PT Putra Kayan Utama Coal.Stages in this study, among others literature studies, observations of the field, then resume the primary data retrieval and secondary. The primary data consist of observation data such as conditions of morphology, litologi,   measurements  of  the  position  of  the  rocks  and  the documentation in the field. While secondary data from topographic maps, geologic model, drilling results, geotechnical data, rainfall data, type and type of the mechanical equipment. Based on the data processing is performed by means of representations of design and calculation using software Minescape 4,119.The design of the bench geometry to the pit, 10 meters high, 5 meters width, slope 45 degrees. The geometry of the high becnh to back fill design, 10 metres high, 20-100 metres width, tilt of 30 degrees (All referring to the recommendation of the Geotechnical PT KPUC). Road plan, on straight condition minimum 22m width, a bend in the road 30 m width, grade maximum 8% and cross slope 37,5 cm. The mining plans, 1st month elevation target RL-130, 140-RL and RL-150 coal mineable 305,068.32 m/ton stripping ratio 3,84:1. Mining 2nd month elevation target RL-160, coal mineable 338,312.33 m/ton, stripping ratio 3.07:1. Mining 3rd month elevation target, RL 10RL 00 and RL-10, coal mineable 263,633.71 m/tons. stripping ratio was 17.13:1. Mining 4th month elevation target RL-30, RL-20, RL-10, RL00 and RL10, coal mineable 277,695.09 m/ton, stripping ratio 13.66:1. Mining 5th month elevation target RL-50, RL-30, RL-20, RL00 and RL10, coal mineable 325,691.87 m/ton, stripping ratio 12,56:1. Mining 6th month elevation target, RL-60, RL-50, RL-40, RL-30 and RL-20, coal mineable 303,461.82 m/ton, the stripping ratio is 1:11.56. Mining 7th month elevation target  RL-70,  RL-60,  RL,  RL-40-30  and  RL-20, coal mineable 309,848.89 m/ton, stripping ratio 6,62:1. Mining 8th month elevation target, RL-70-50 and RL-40, coal mineable 312,352.19 m/ton, stripping ratio 9.80:1. Mining 9th month elevation target RL-90, RL -80, RL-70  and RL-60, coal mineable 305,775.60 m/ton, stripping ratio 10,66:1. Mining 10th month elevation target RL-90, RL-80, RL-70 and RL-60, coal mineable 401,871.08 m/ton, stripping ratio 9,93:1.Mining 11th month elevation target RL-90 and RL-80, coal mineable 459,093.08 m/ton, stripping ratio 11.11:1. Mining 12th month elevation target RL-90, RL-100 and final design yearly, coal mineable 499,331.65 m/ton,  stripping ratio  7.28:1.  Total coal mineable reserves 4,101,504.49 tons and the volume total is 39,223,102.36 Bcm of overburden and will be fill back to pit10 and pit3, total stripping ratio 9,56:1.